An Analysis on the Themes and Cross Cultural Conflict in Bharati Mukherjee’s Novels: Exploring Cultural Conflict and Diasporic Identity in Bharati Mukherjee's Novels (Journal of Advances and Scholarly Researches in Allied Education, 2018)
This paper, extends how Indian writing in English has happened to its own owing no loyalty to British Literature. It talks about the development and development of novel first in the hands of men. It makes a directed reference toward the novel composed by women, particularly Bharati Mukheijee and her place in the circle of Indian fiction as a diasporic writer. It additionally talks about how the life of Bharati Mukherjee leaves an engraving on her works, how the effect of her family shaped her viewpoint and furthermore how her fictional virtuoso uncovers itself in her adolescent creations prompting full-length novels winning her honors and awards. Bharati Mukherjee portrays a cross-cultural crisis looked by her women characters in her novels. This paper likewise follows the yawning break between the lifestyles driving the characters in her novels to a sentiment of wretchedness and disappointment causing a cultural stun. It inspects how the women characters are gotten between the two universes, the one they abandoned and the other they have come to. It follows how the hero in the entirety of her novel is a lady and an exile and the development of the plot is accomplished by the gadget of voyage starting with one nation and cultural milieu then onto the next.